Agri-food supply chains during the COVID-19 pandemic in Europe and Italy. A challenge between food security, recovery and market dinamics, labour and consumer protection, Green Deal and climate uncertainty - D’Addezio, Mariarita (Przegląd Prawa Rolnego, 2021)
The article examines, first of all, the regulations that the European Union and Italy have adopted to support agri-food supply chains and market recovery after the downturn caused by the COVID-19 pandemic. The author then focuses on the delicate relationship between the agri-food sector and the climate change and its impact on the agri-food sector and its impact on the agri-food sector, as well as on the other causes that are currently threatening its productive capacity. The need for its sustainable ecological development, as well as for greater protection of food sovereignty is also stressed.